The Association between Resolvin D1 Levels and Gestational Diabetes Mellitus: Implications for Perinatal Outcomes - Seyhanli, Zeynep; Bayraktar, Burak; Bucak, Mevlut; Karabay, Gulsan; Tokgoz Cakir, Betul; Ulusoy, Can Ozan; Aktemur, Gizem; Sefik, Selver Ozge; Topkara Sucu, Serap; Celen, Sevki; Caglar, Ali Turhan (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: To evaluate maternal Resolvin D1 levels in women with gestational diabetes mellitus (GDM) and investigate the association between perinatal outcomes. STUDY DESIGN: This case-control study included 88 singleton pregnancies, conducted from August 2023 to January 2024, at a tertiary care center. Participants were divided into two groups: 44 pregnant women diagnosed with GDM comprised the study group, and 44 healthy pregnant women served as the control group. Additionally, the GDM group was categorized based on management approach into 21 women managed with diet alone and 23 women requiring insulin therapy. Maternal plasma Resolvin D1 levels and maternal-neonatal outcomes were then compared between groups. The analysis involved determining the optimal Resolvin D1 cut-off levels for predicting composite adverse neonatal outcomes in GDM using receiver operating characteristic curve (ROC) analysis. RESULTS: The plasma Resolvin D1 level in pregnant women with GDM was significantly higher compared to the control group (337±74.1 vs. 297±56.7, p<0.001). Furthermore, maternal plasma Resolvin D1 levels were associated with composite adverse neonatal outcomes [presence of at least one of the following conditions: preterm birth (<37 weeks), low birth weight (LBW) (<2500 grams), neonatal hypoglycemia, hyperbilirubinemia, APGAR score at 5th minute <7, respiratory distress syndrome (RDS), and admission to the neonatal intensive care unit (NICU)], with a cut-off of >338.75, showing a sensitivity of 56.3%, a specificity of 79.2%, and an AUC of 0.675 (95% CI: 0.567-0.771, p=0.024). CONCLUSIONS: This study demonstrated that pregnancies affected by GDM exhibit elevated levels of Resolvin D1, which is associated with a higher incidence of composite adverse neonatal outcomes.